ANALISIS PERBANDINGAN PENGGUNAAN BIODIESEL B35 DAN B40 TERHADAP KINERJA MOTOR DIESEL DI PLTMG SERAM PEAKER - Adi Septi La Idi; Kristofol Waas; Clay Talakua (Department of Mechanical Engineering, 2025)
This study analyzes the effect of using B35 and B40 blended biodiesel fuels on the performance of a MAN 12V 51/60 DF diesel engine at the Seram Peaker Gas Engine Power Plant (PLTMG). The background for this research is the national mandatory biodiesel policy, which continues to increase its blend ratio. The results show that by using 1 kg of fuel, the B35 blend can produce 12.486 MW of power with a fuel consumption of 0.2100 kg/kWh, an effective thermal efficiency of 20.31%, and a mechanical efficiency of 0.91092. Meanwhile, the B40 blend produces 12.367 MW with a higher fuel consumption of 0.21884 kg/kWh, an effective thermal efficiency of 18.92%, and a mechanical efficiency of 0.887581. These data indicate that increasing the biodiesel content from B35 to B40 tends to decrease the power output and engine efficiency, while fuel consumption increase. Keywords: Biodiesel, B35, B40, Diesel Engine Performance.